Fundamental electrical and electronic principles - Robertson, Christopher R. (Newnes, 2008)
A thorough introduction to electrical and electronic engineering at Level 3.
Previous edition: 2001.
1st ed. published as: Electrical and electronic principles.
Obsahuje index.
Keywords: elektrotechnika; elektronika; electric engineering; electronics; elektronické knihy; učebnice; electronic books; textbooks